Urgensi Penggunaan Rencana Proses Pembelajaran (RPP) Dalam Pembelajaran Ilmu Pengetahuan Sosial (IPS) Di Sekolah Dasar - Mae saroh; Riska Oktaviani Saputri; Isna Rahmawati; Afifah Shalihah; Amin Supartin; Annisa Seffie Isnanty; Latifatuz Zahro (Academica: Journal of Multidisciplinary Studies, 2023)
The design of the learning process (Rencana Proses Pembelajaran/ RPP) is one of the important steps that must be prepared and planned by the teacher before starting the learning process in the classroom. Whether or not the learning process runs smoothly is also influenced by the existence of lesson plans. Therefore the purpose of this study was to determine the effectiveness of the implementation of learning using RPP and the importance of implementing RPP in classroom learning. This research is included in a descriptive qualitative study conducted at state elementary school 2 Kartasura, grade 4. Research data was collected using the following techniques: 1) Interviews with teachers and principals, 2) Analysis of lesson plans for social studies, 3) Observation during learning, 4) study related research literature. From the results of the study it can be seen that the use of RPP that are in accordance with learning materials, student characteristics and student competencies can increase the effectiveness of learning in the classroom. In addition, the use of RPP is also able to assist teachers in developing strategies, models, media and methods used in learning, especially social studies material which tends to be standard and boring.